2004
DOI: 10.1177/154411130401500506
|View full text |Cite
|
Sign up to set email alerts
|

VirulenceFactors ofEnterococcus faecalis:Relationship toEndodonticDisease

Abstract: Enterococcus faecalis is a micro-organism that can survive extreme challenges. Its pathogenicity ranges from life-threatening diseases in compromised individuals to less severe conditions, such as infection of obturated root canals with chronic apical periodontitis. In the latter situation, the infecting organisms are partly shielded from the defense mechanisms of the body. In this article, we review the virulence factors of E. faecalis that may be related to endodontic infection and the periradicular inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
253
0
29

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 394 publications
(285 citation statements)
references
References 191 publications
(207 reference statements)
3
253
0
29
Order By: Relevance
“…18 There is evidence that the presence of E. faecalis in teeth with filled canals, cases of chronic apical periodontitis, 24 and infections after endodontic treatments are due to its high resistance to antimicrobials, 3,21 its survival for long periods in environments deprived of nutrients and oxygen, 24 and its high virulence. These characteristics of E. faecalis are likely a result of its production of aggregation substances, surface adhesins, extracellular superoxide, lytic enzyme gelatinase, and hyaluronidase.…”
Section: Discussionmentioning
confidence: 99%
“…18 There is evidence that the presence of E. faecalis in teeth with filled canals, cases of chronic apical periodontitis, 24 and infections after endodontic treatments are due to its high resistance to antimicrobials, 3,21 its survival for long periods in environments deprived of nutrients and oxygen, 24 and its high virulence. These characteristics of E. faecalis are likely a result of its production of aggregation substances, surface adhesins, extracellular superoxide, lytic enzyme gelatinase, and hyaluronidase.…”
Section: Discussionmentioning
confidence: 99%
“…the enterococcal surface protein, Esp) and aggregation substances (Aggs) (reviewed by Kayaoglu & Østavik, 2004). Esp was found to be enriched in infectionderived enterococcal strains (Shankar et al, 1999) and it is associated with enhanced adhesion to abiotic surfaces and biofilm formation by E. faecalis (Toledo-Arana et al, 2001;Tendolkar et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Several traits of E. faecalis are described as virulence factors (reviewed by Kayaoglu & Østavik, 2004), and adhesion to biotic and abiotic surfaces is one of them. E. faecalis is one of the predominant organisms found in biofilms in clogged biliary stents, used to palliate obstructions of the biliary and pancreatic ducts (Dowidar et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…E. faecalis has displayed resistance to a wide range of antibiotics [15]. Moreover, it has been found that the effective proton pump mechanism which maintains optimal cytoplasmic pH levels of these species may participate in their resistance to the antimicrobial effects of calcium hydroxide [54].…”
Section: Discussionmentioning
confidence: 99%
“…E. faecalis, in particular, is difficult to remove owing to its considerable virulence factors constituting a source of recurrent infection after conservative as well as surgical treatments [15]. P. acnes is an anaerobic Grampositive bacterium responsible for a wide range of infections and inflammatory conditions [16].…”
Section: Introductionmentioning
confidence: 99%